Evaluasi Terapi Antibiotik pada Pasien yang Didiagnosis Sepsis di ICU RSUD dr. Mohamad Soewandhie berdasarkan Metode Gyssens - Ristanti, Safira; Adiwinoto, Ronald Pratama; Wijaya, Rike Andy; Putro, Saptono (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
ABSTRACT In the high-stakes world of Intensive Care Units (ICUs), the judicious application of empirical antibiotic therapy is crucial for managing sepsis in critically ill patients, as its misuse is often linked with unfavorable patient outcomes. Thus, timely and precise treatment strategies are indispensable. This study was designed to evaluate the rationality of such treatments among sepsis patients at RSUD Dr. Mohamad Soewandhie between January 2021 and September 2024. Using an observational and descriptive approach, researchers scrutinized secondary data from 120 patient medical records, with expert reviewers employing the Gyssens method to assess treatment rationality. Findings revealed that 60% of patients received appropriate empirical antibiotic therapy, most commonly intravenous Ceftriaxone. Alarmingly, culture and antibiotic sensitivity tests were conducted on only 18 patients, yielding 11 positive results, and among these were 19 gram-negative and 2 gram-positive bacterial isolates, with a troubling 67.9% being multidrug-resistant organisms (MDRO). Despite the empirical therapy's rationality, the study noted a concerning mortality rate of 81.67%, possibly owing to delays in obtaining culture results and the use of outdated local guidelines for antibiotic therapy in sepsis management, highlighting gaps in existing approaches. Keywords:Empirical Antibiotic Therapy, Intensive Care Unit, Sepsis, Septic Shock, Gyssens Method